Resistance through inhibition: ectopic expression of serine protease inhibitor offers stress tolerance via delayed senescence in yeast cell - Joshi, Rakesh S.; Tanpure, Rahul S.; Singh, Rajan Kumar; Gupta, Vidya S.; Giri, Ashok P. (Biochemical and Biophysical Research Communications, 2014)
Protease inhibitors have been known to confer multiple stress tolerance in transgenic plants. We have assessed growth of yeast (Pichia pastoris GS115) strains expressing inhibitory repeat domains (PpIRD(+)) of previously characterized Capsicum annuum protease inhibitors under high salt, heavy metal and oxidative stress. PpIRD(+) strains exhibited multiple stress tolerance and showed differential molecular responses at transcriptional and translational level on exposure to stress inducing agents like heavy metal, high salt and H2O2. PpIRD(+) strains display significant reduction in metacaspase (Yca1) activity, the key enzyme in apoptosis, indicates the possibility of cross reactivity of IRDs (serine protease inhibitor) with cysteine proteases. PpIRD(+) and Saccharomyces cerevisiae knockout with Yca1 (Delta Yca1) strain showed similar growth characteristics under stress, which indicated the delayed senescence due to cellular metacaspase inhibition. Molecular docking study showed a close proximity of IRDs reactive site and the active site of metacaspase in the complex that signified their strong interactions. Maintenance of GAPDH activity, primary target of metacaspase, in PpIRD(+) strain evidenced the inhibition of metacaspase activity and survival of these cells under stress. This report demonstrates a potential molecular mechanism of protease inhibitor-based multiple stress tolerance in yeast strains. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Metacaspase; Multiple stress tolerance; protease inhibitor; Yeast